The Roles of Exosomes as Future Therapeutic Agents and Diagnostic Tools for Glioma - Wu, Xiaoben; Wang, Xingbang; Wang, Jing; Hao, Yingying; Liu, Fang; Wang, Xin; Yang, Lei; Lu, Zhiming (Frontiers in Oncology, 2021)
Glioma is a common type of tumor originating in the brain. Glioma develops in the gluey supporting cells (glial cells) that surround and support nerve cells. Exosomes are extracellular vesicles that contain microRNAs (miRNAs), messenger RNA (mRNA), and proteins. Exosomes are the most prominent mediators of intercellular communication, regulating, instructing, and re-educating their surrounding milieu targeting different organs. As exosomes' diameter is in the nano range and the ability to cross the blood-brain barrier (BBB), a crucial obstacle in developing therapeutics against brain diseases, including glioma, makes the exosomes a potential candidate for delivering therapeutic agents for targeting malignant glioma. This review communicates the current knowledge of exosomes' significant roles that make them crucial future therapeutic agents and diagnostic tools for glioma.